Yurisdiksi International Criminal Court dalam Penyelesaian Kasus Kejahatan Perang Oleh Kepala Negara - Pesurnay, Dominique Geraldine Grizelda; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (Faculty of Law Universitas Pattimura, 2024)
On March 27, 2023, the International Criminal Court issued a warrant for the arrest of the Russian Head of State, Vladimir Putin, for alleged war crimes committed in Ukraine. Russia itself is not a member state of the 1998 Rome Statute so this case highlights the contradictions in the application of the International Criminal Court's jurisdiction and the enforcement of international humanitarian law under the 1998 Rome Statute. The purpose of the research is to analyze and find out whether the status of a state that does not ratify the 1998 Rome Statute affects the validity of the arrest warrant of the head of state issued by the International Criminal Court and the settlement of war crimes cases by the head of state according to the International Criminal Court. The research method that the author uses is normative juridical research method as well as, statutory approach, case approach and conceptual approach. The results of this study show that the International Criminal Court has four types of jurisdiction: personal, material, temporal, and territorial. If a state is unwilling or unable to address these issues, then the International Criminal Court's jurisdiction will apply. In Vladimir Putin's case, his war crimes on Ukrainian territory fall within the territorial jurisdiction of the International Criminal Court, making the arrest warrant issued automatically valid. Heads of state, as high-ranking government officials, are treated as equals before the International Criminal Court, as emphasized in Article 27 of the 1998 Rome Statute. The case resolution procedure would then be the preliminary examination, investigation, pre-trial stage, trial stage, appeal stage, and sentencing. Vladimir Putin will enter the pre-trial stage after his arrest.